Concept of Size-Dependent Atomic Interaction Energies for Solid Nanomaterials: Thermodynamic and Diffusion Aspects - Shirinyan, Aram S. (Металлофизика и новейшие технологии, 2015)
Energy-related problems of solid nanoparticles and nanoscale materials concerning their stability and structure are investigated with a specifically targeting on nanocrystalline metallic systems. The new concept based on the atomic hypothesis about the size dependence of nearest atom—atom interaction energy and co-ordinated actions of atoms is offered. The verification is done for metallic thin films and nanoparticles on the basis of experimental results, theoretical approach, and molecular static simulations. As shown, for nanomaterials, the concepts of size-dependent interatomic interaction energies can be used for description of thermodynamic and kinetic properties.